Applications of molecular dynamics simulation in biomolecular folding and recognition - Ng, Justin Tze Yang (Nanyang Technological University, 2020)
Proteins are an important class of biomolecules essential for life. They are involved in many biological functions, such as cell signalling, transport, defence mechanisms etc. Proteins must undergo two processes, namely folding and biomolecular recognition, in order to effectively perform their functions. Molecular Dynamics Simulations have been demonstrated as a successful tool used complementary to experimental methods in the understanding of biological processes. The projects in this thesis involve the application of Molecular Dynamics simulations in the study of various aspects of protein folding and biomolecular recognition.